Interprofessional education applied in first-year and third-year health students: cross-sectional study - Perwitasari, Dyah Aryani; Baroroh, Faridah; Sari, Andriana; Novitasari, Putri Rachma; Kodriati, Nurul; Matahari, Ratu; Purwanto, Barkah Djaka (Pharmaciana, 2023)
Health professions work together to provide the best service in health care facilities by collaborating with patients, families, worker and the community. Interprofessional education (IPE) were practice of collaboration between two or more students from different health profession programs. The purpose of study was to compare IPE results from first and third year batches. The two batches included 345 first-year students and 460 third-year students, from three different health disciplines, including medicine, pharmacy, and public health. These students met for four weeks to increase interprofessional collaboration, improve communication skills, foster respect and increase knowledge of the various roles each discipline, especially case management, conflict management and team work. Before IPE program, the students were given pre-questionnaire to assess their prior understanding of IPE. Each group of first-year students presented the outcomes of their discussions in the fourth week, while the third-year students created a poster about the subject and presented it in the second week. The students complete the program and post-questionnaire after their presentation. The International Collaborative Competencies Attainment Survey served the development the IPE questionnaire (ICCAS). The result of pre-IPE domains’ score revealed substantial disparities in the team work domain, with third-year students score was lower than the first students, whereas first-year students had the highest score in the most of IPE categories, unless collaboration and conflict management (p>0.05). The post-IPE domains’ score showed significant differences in all of the domains. Most of the IPE domains had higher score in first year students, excluding communication and team work.